Concise Review: Liver Regenerative Medicine: From Hepatocyte Transplantation to Bioartificial Livers and Bioengineered Grafts. (2nd October 2016) - Nicolas, Clara T.; Hickey, Raymond D.; Chen, Harvey S.; Mao, Shennen A.; Lopera Higuita, Manuela; Wang, Yujia; Nyberg, Scott L.
Abstract : Donor organ shortage is the main limitation to liver transplantation as a treatment for end-stage liver disease and acute liver failure. Liver regenerative medicine may in the future offer an alternative form of therapy for these diseases, be it through cell transplantation, bioartificial liver (BAL) devices, or bioengineered whole organ liver transplantation. All three strategies have shown promising results in the past decade. However, before they are incorporated into widespread clinical practice, the ideal cell type for each treatment modality must be found, and an adequate amount of metabolically active, functional cells must be able to be produced. Research is ongoing in hepatocyte expansion techniques, use of xenogeneic cells, and differentiation of stem cell-derived hepatocyte-like cells (HLCs). HLCs are a few steps away from clinical application, but may be very useful in individualized drug development and toxicity testing, as well as disease modeling. Finally, safety concerns including tumorigenicity and xenozoonosis must also be addressed before cell transplantation, BAL devices, and bioengineered livers occupy their clinical niche. This review aims to highlight the most recent advances and provide an updated view of the current state of affairs in the field of liver regenerative medicine.